Purtscher's Retinopathy - Anil Kumar Verma; Rajeev Tuli; Gaurav Sharma; Deepak Sharma (Delhi Journal of Ophthalmology)
Purtscher's retinopathy, a indirect ocular injury, presents with multiple patches of superficial retinal whitening and retinal hemorrhages surrounding the optic nerve. The optic disc may appear normal initially but an afferent pupillary defect may be present and later on optic disc pallor may develop. Two similar cases of Purtscher's retinopathy with fundus photographs are being reported in this article